Nociceptor-expressed ephrin-B2 regulates inflammatory and neuropathic pain - Kullander Klas; Lagerström Malin C; Nassar Mohammed A; Cendan Cruz M; Yuan Guanglu; Zhao Jing; Gavazzi Isabella; Wood John N (SAGE Publishing, 2010)
Abstract Background EphB receptors and their ephrin-B ligands play an important role in nervous system development, as well as synapse formation and plasticity in the adult brain. Recent studies show that intrathecal treatment with EphB-receptor activator ephrinB2-Fc induced thermal hyperalgesia and mechanical allodynia in rat, indicating that ephrin-B2 in small dorsal root ganglia (DRG) neurons and EphB receptors in the spinal cord modulate pain processing. To examine the role of ephrin-B2 in peripheral pain pathways, we deleted ephrin-B2 in Nav1.8+ nociceptive sensory neurons with the Cre-loxP system. Sensory neuron numbers and terminals were examined using neuronal makers. Pain behavior in acute, inflammatory and neuropathic pain models was assessed in the ephrin-B2 conditional knockout (CKO) mice. We also investigated the c-Fos expression and NMDA receptor NR2B phosphorylation in ephrin-B2 CKO mice and littermate controls. Results The ephrin-B2 CKO mice were healthy with no sensory neuron loss. However, pain-related behavior was substantially altered. Although acute pain behavior and motor co-ordination were normal, inflammatory pain was attenuated in ephrin-B2 mutant mice. Complete Freund's adjuvant (CFA)-induced mechanical hyperalgesia was halved. Formalin-induced pain behavior was attenuated in the second phase, and this correlated with diminished tyrosine phosphorylation of N-methyl-D-aspartic acid (NMDA) receptor subunit NR2B in the dorsal horn. Thermal hyperalgesia and mechanical allodynia were significantly reduced in the Seltzer model of neuropathic pain. Conclusions Presynaptic ephrin-B2 expression thus plays an important role in regulating inflammatory pain through the regulation of synaptic plasticity in the dorsal horn and is also involved in the pathogenesis of some types of neuropathic pain.